IMPLIKASI KUALITAS INFORMASI KEUANGAN DAN PENGAMBILAN KEPUTUSAN TERKAIT DENGAN KONSEP TEORI AKUNTANSI DALAM BISNIS MODERN - Aji, Gunawan; Amna, Fikrotul; Kholisah , Nur; Mangesti, Fadrika Hening (Kampus Akademik Publiser, 2024)
This research aims to explore the implications for the quality of financial information and decision making related to the concept of accounting theory in the context of modern business. Literature study which involves searching and analyzing various relevant sources such as books, journals and related articles is the method in this research. The research results show how important accounting theory is to strengthen sustainable accounting processes in today's fast-paced and complex economic world. The conclusion obtained is that it is important for companies to continue to develop and use the principles of accounting theory in daily company operations, so that they can make better and more effective decisions. Keywords: Modern Business, Technological Development, Accounting Theory